A semi-quantitative structural evaluation framework for corrosion-damage reinforced concrete bridge columns. (1st July 2021) - Mohammed, Amina; Almansour, Husham; Martin-Perez, Beatriz
Highlights: A semi-quantitative assessment framework is to evaluate corroded bridge columns using limit states. The proposed framework suggests the use of structural performance thresholds. The framework provides a systematic assessment procedure needs minimum numerical efforts. The framework can be integrated into the bridge management system. The framework presents a step towards the development of a fully quantitative assessment approach. Abstract: A semi-quantitative assessment framework (SQAF) is proposed to evaluate slab-on-girder bridge columns subjected to reinforcement corrosion using evaluation limit states (ultimate limit state, including seismic loads for high seismic zones, and serviceability limit state). The SQAF suggests the use of structural performance thresholds decided by the evaluation engineers based on the bridge management system (BMS) requirements. The SQAF provides a systematic assessment procedure that needs minimum numerical efforts and can be integrated into the BMS. Although the framework is dependent on the accuracy of the input data, which in turn depends on enhanced inspection and material testing, it presents a step towards the development of a fully quantitative assessment approach. The proposed assessment framework provides efficient analysis tools that help to quantify the important performance parameters of aged slab-on-girder bridge columns. The quantitative comparisons between the required and existing load capacities and performance measures would give the bridge owners, practicing engineers, and bridge management team a better evaluation approach that would reduce the maintenance/rehabilitation cost and provide higher safety.